Determinant of Demand for Takaful Cash Waqf in Malaysia - Abdul Hamid, Mohamad; Ithnain, Suzana; Abd Rahman, Ishak (Journal of Advanced Research in Business and Management Studies, 2020)
The study investigates the relationships between consumer behavior, consumer awareness and religiosity influence on intention to demand for Takaful cash Waqf. The respondents of the study comprise 100 individual contribute as a participant in Takaful/insurance. The result of the study shows that there is a positive relationship between consumer behaviors and religiosity influence on intention to demand for Takaful cash Waqf. The study found that consumer awareness is relatively not significance with determinant demand for Takaful, while consumer behavior and religiosity is strong relationship. The implication from this study shows that there is a need for sharing more information about cash Waqf if Takaful really want to implement Takaful cash Waqf as a product. The study proposes that Takaful should educate the public to increase the awareness of Takaful Cash Waqf.